Design and Behavior: Evaluating Performance of Student Lounge through Behavior Mapping - Kiki Putri Amelia; Togar Mulya Raja; Hendi Anwar; Parlindungan Revalino (Jurnal Riset Arsitektur, 2026)
Student lounge is a primary communal space within the campus area that supports students’ academic, social, and recreational activities. This study aims to evaluate spatial performance based on users’ actual activities using a qualitative method with a behavior mapping approach. A place-centered mapping method was employed to analyze spatial performance by identifying behavior patterns, intensity of space use, and user satisfaction with spatial quality. Data were collected through field observations, behavior mapping, documentation, and structured questionnaires distributed to students. The results indicate that spatial configuration and seating facilities have a significant influence on the intensity of social interactions, duration of space use, and the formation of user activities. These findings highlight the importance of activity-based design evaluation in designs of student lounges that are responsive and inclusive.